HUBUNGAN RIWAYAT PENYAKIT KELUARGA, KEBIASAAN MEROKOK DAN KONSUMSI ALCOHOL DENGAN FAKTOR RISIKO SINDROM METABOLIK - Nuryani; Marselia Sandalayuk (MEDIA ILMU KESEHATAN, 2020)
Background: Metabolic Syndrome is characterized by visceral obesity, increased triglycerides and glucose, low high lipoprotein density, hypertension. Objective: Identify factors associated with metabolic syndrome.Methods: The observational analytic was using a cross sectional study which was conducted in Telaga Biru Health Center. The number of samples 319 people was collected by purposive sampling. Data analysis using chi square test.Results: The prevalence of metabolic syndrome was 6.0%, hypertension 62.1%, central obesity 53.9% and hyperglycemia 15.4%. There was not association between smoking, alcohol consumption, family history of obesity with hypertension, but there was significant association between family history of hypertension and diabetes mellitus. There was not association between alcohol consumption and family history of obesity with central obesity, but there was significant association between smoking habits, family history of hypertension, obesity and diabetes mellitus. There was not association between smoking habits, history of alcohol consumption, family history of hypertension and diabetes mellitus with hyperglycemia, but there was significant association between family history of obesity.Conclusion: There was significant association between family history of hypertension, diabetes mellitus with hypertension. There was association smoking habits, family history of hypertension, obesity and diabetes mellitus with central obesity. There was significant association between family history of obesity with hyperglycemia.